Simulação da dispersão de alumina no Centro de Lançamento de Alcântara em diferentes condições de estabilidade atmosférica - Rosa, Larissa Coutinho (2017)
The main objective of this work was to simulate the dispersion of the aluminum oxide particulate material during and after the launching of rockets at the Alcantara launch center in the state of Maranhão. It was used the mesoscale meteorological model, WRF, and the rocket effluent simulator model, MSDEF. The meteorological data of the region obtained through the WRF served as input parameters for the MSDEF model. In order to analyze the results obtained by the WRF, radiosonde data were collected between the dry and rainy periods of the year 2013. For the same period, the data were simulated using the WRF software. The analyzes are contemplated from days 18 to 21 of the month of March (rainy season) and by the same days for September (dry period). Subsequently, the parameters obtained by the meteorological modeling were used as input to simulate the dispersion of the aluminum oxide. It can be affirmed that the main objective and the specific objectives of this work were successfully achieved, showing that it is possible to use the mesoscale meteorological model, WRF to generate input data to the MSDEF. It is important to note that this modeling system can be applied to any rocket launch case anywhere in the world for simulations and pre and post-launch analyzes of the environmental effects of rocket launch operations.